ANALISIS FAKTOR-FAKTOR KESEJAHTERAAN SUBJEKTIF DALAM KALANGAN PESERTA MIKRO KREDIT AMANAH IKHTIAR MALAYSIA (AIM): CAWANGAN KEPONG, WILAYAH SELANGOR DAN KUALA LUMPUR TENGAH - Nik Mad, Nik Shahrizan; Md Yunus, Marzudi; Abdul Azziz, Muhammad Shamshinor (JURNAL MELAYU SEDUNIA, 2020)
People’s views and perceptions of well-being are different from one another. These views and perceptions are based on experiences, evaluations and expectations based on the journey of human life. In addition, the process of socialization, environment and culture also affects perception and the way people perceive their lives. The level of well-being is measured based on the satisfaction and quality of life. This study evaluated the subjective well-being factors of the participants of AIM and examined their views on the impact in their lives. The subjective well-being index used in this study is a set of several indices used locally and abroad. This index is selected and customized based on the needs of Malaysians. Based on this index, 13 factors that impacted life the most were selected and used in this study. These factors were analyzed using Models 3P and 3E in which the subjective well-being component was evaluated based on a global assessment based on the time travel of human life and the psychological impact of the experience.